Recent Advances in Synthetic Chemical Inducers of Plant Immunity - Zhou, Mian; Wang, Wei (Frontiers in Plant Science, 2018)
Different from the conventional biocidal agrochemicals, synthetic chemical inducers of plant immunity activate, bolster or prime plant defense machineries rather than directly acting on the pathogens. Advances in combinatorial synthesis and high-throughput screening methods have led to the discovery of various synthetic plant immune activators as well as priming agents. The availability of their structures and recent progress in the mechanistic understanding of plant immune responses have opened up the possibility of identifying new or more potent chemical inducers through rational design. In this review, we first summarize the chemical inducers identified through large-scale screening and then discuss the emerging trends in the identification and development of novel plant immune inducers including natural elicitor based chemical derivation, bifunctional combination and computer-aided design.